Viral Communities in the Global Deep Ocean Conveyor Belt Assessed by Targeted Viromics - De Corte, Daniele; Martínez, Joaquín Martínez; Cretoiu, Mariana Silvia; Takaki, Yoshihiro; Nunoura, Takuro; Sintes, Eva; Herndl, Gerhard J.; Yokokawa, Taichi (Frontiers in Microbiology, 2019)
Viruses are an abundant, diverse and dynamic component of marine and terrestrial ecosystems. In the ocean, viruses play a key role in the biogeochemical cycles and controlling microbial abundance, diversity and evolution. Recent metagenomics studies assessed the structure of the viral community in the upper ocean. However, little is known about the compositional changes in viral communities along the deep ocean conveyor belt. To assess potential changes in the viral community in the global deep-water circulation system, water samples were collected in the core of the North Atlantic Deep Water (~2,500 m) and Pacific Antarctic Bottom Water (~4,000 m). Microbial and viral abundance were evaluated by flow cytometry. Subsequently, flow cytometry was used to sort virus-like particles and next generation sequencing was applied to build DNA libraries from the sorted virus populations. The viral communities were highly diverse across different oceanic regions with high dissimilarity between samples. Only 18% of the viral protein clusters were shared between the North Atlantic Deep Water and the Pacific Antarctic Bottom Water. Few viral groups, mainly associated with uncultured environmental and uncultured Mediterranean viruses were ubiquitously distributed along the global deep-water circulation system. Thus, our results point to a few groups of widely distributed abundant viruses in addition to the presence of rare and diverse types of viruses at a local scale.